2012
DOI: 10.2215/cjn.00390112
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Dose Scaled to Body Surface Area and Size-Adjusted, Sex-Specific Patient Mortality

Abstract: SummaryBackground and objectives When hemodialysis dose is scaled to body water (V), women typically receive a greater dose than men, but their survival is not better given a similar dose. This study sought to determine whether rescaling dose to body surface area (SA) might reveal different associations among dose, sex, and mortality.Design, setting, participants, & measurements Single-pool Kt/V (spKt/V), equilibrated Kt/V, and standard Kt/V (stdKt/V) were computed using urea kinetic modeling on a prevalent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 28 publications
(32 reference statements)
9
37
0
Order By: Relevance
“…Daugirdas et al have shown that BSA-based dialysis dosing will result in higher delivered dialysis doses to women and small men 23 . A recent study has also shown a better relationship with survival for the BSA-based dosing compared to current practice 24 . On the other hand, Morton and Singer have argued that the dialysis dose should be based on metabolic rate because of the non-linear correlation between body mass and metabolic rate 25 .…”
Section: Discussionmentioning
confidence: 96%
“…Daugirdas et al have shown that BSA-based dialysis dosing will result in higher delivered dialysis doses to women and small men 23 . A recent study has also shown a better relationship with survival for the BSA-based dosing compared to current practice 24 . On the other hand, Morton and Singer have argued that the dialysis dose should be based on metabolic rate because of the non-linear correlation between body mass and metabolic rate 25 .…”
Section: Discussionmentioning
confidence: 96%
“…The greatest differences between measured TBW by MF-BIA and that estimated by anthropometric equations occurred in patients with similar BMI, but with more fat and reduced muscle mass. This may help to explain the apparent paradox of increased survival for the very obese haemodialysis patients in North America compared to those with a normal BMI [36], as the patients have proportionately much more fat and so to achieve an adequate Kt/V based on anthropometric equations, they require more prolonged dialysis sessions, potentially increasing sodium and middle molecular weight clearances [37]. On the other hand, underdosing of various groups could also occur, because on multiple regression analysis, the difference between measured and calculated TBW was affected by pre-dialysis serum albumin, BMI and percentage skeletal muscle mass as well as diabetic status, sex and ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies, including HEMO and the study by Ramirez et al (see their Figure 2), show that larger patients have lower mortality rates independent of dialysis dose and often attributed to better nutrition (3,(11)(12)(13). When corrected for this effect, Kt/V shows an even steeper relationship to mortality (14).…”
Section: Choices For a Size-normalizing Denominatormentioning
confidence: 99%
“…When corrected for this effect, Kt/V shows an even steeper relationship to mortality (14). Ramirez et al corrected for this effect using an anthropometric estimate of V (Vant) and found little influence on survival in their cohort (3). Regardless of the reason for the effect of size on outcome, any attempt to normalize the dialysis dose to body size must take into consideration this potential confounder.…”
Section: Choices For a Size-normalizing Denominatormentioning
confidence: 99%
See 1 more Smart Citation